2019
DOI: 10.1590/1807-3107bor-2019.vol33.0118
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and factors associated with the caries experience in adults – a population-based study in Brazil

Abstract: The objective of this study was to investigate the experience of caries related to social capital and associated factors in adults in large-scale population-based study. A Cross-sectional study was performed in 163 municipalities in the State of São Paulo, Brazil (SBSP-2015). 17,560 people were evaluated, of which 6051 were adults aged 35-44 years. Hierarchical logistic regression analysis was proposed. Outcome variables (decayed teeth, missing teeth and DMFT) and independent variables were included in the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…When disadvantaged subjects were compared with the general population, they had a higher level of caries. Low-income subjects, indeed, have a double probability of suffering from caries (OR 2.2 [95% CI 1.7–2.7], p < 0.05; 6524 participants, two studies) [ 56 , 57 ], while subjects with a low level of education showed a greater than one and a half times probability (OR 1.6 [95% CI 1.42–1.9], p < 0.05; 5653 participants) [ 57 ], with a similar odds ratio to immigrants (OR 1.66 [95% CI 1.29–2.13], p < 0.05; 3738 participants) [ 58 ] and individuals living in rural areas (OR 1.6 [95% CI 1.2–4.3], p = 0.01; 280 participants) [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When disadvantaged subjects were compared with the general population, they had a higher level of caries. Low-income subjects, indeed, have a double probability of suffering from caries (OR 2.2 [95% CI 1.7–2.7], p < 0.05; 6524 participants, two studies) [ 56 , 57 ], while subjects with a low level of education showed a greater than one and a half times probability (OR 1.6 [95% CI 1.42–1.9], p < 0.05; 5653 participants) [ 57 ], with a similar odds ratio to immigrants (OR 1.66 [95% CI 1.29–2.13], p < 0.05; 3738 participants) [ 58 ] and individuals living in rural areas (OR 1.6 [95% CI 1.2–4.3], p = 0.01; 280 participants) [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…In all three types of disadvantaged individuals in whom caries experience was compared with the general population, DMFT was higher in socially vulnerable people. Specifically, a greater probability of having a higher DMFT index was found in low-education people (OR 1.40 [95% CI 1.29–1.52], p < 0.05; 6051 participants) [ 57 ], in low-income people (OR 3.7 [95% CI 2.8–4.6], p < 0.05; 1695 participants, two studies, I 2 = 78%) [ 56 , 76 ] and in professionals who sustain an excessive hourly workload (>40 h of overtime) (OR 2.56 [95% CI 1.23–5.33] p = 0.012 to OR 3.01 [95% CI 1.13–7.97] p = 0.027; 950 participants) [ 79 , 80 ]. Moreover, institutionalized elderly people (resident in care homes) showed a higher caries experience than non-institutionalized elderly people with a DMFT 25.4 SD 2.1 ([95% CI 19.9–30.9]; 2608 participants, six studies) versus 16.1 SD 2.1 ([95% CI 11.2–21]; 8276 participants, nine studies) [ 29 , 31 , 34 , 40 , 41 , 44 , 48 , 60 , 61 , 63 , 64 , 81 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the individual factors, the use of dental services has also been linked to broader social determinants, such as social capital, referring to attributes of social structure that facilitates the actions of individuals [ 2 , 6 ]. There has been increasing evidence for the influence of social capital on oral health [ 7 , 8 , 9 , 10 , 11 ]. Two dimensions of social capital include the structural (measured by social network, civic engagement) and cognitive (measured by trust, reciprocity) dimensions [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examiner training procedures, data collection methods and the variables included in the study were previously described in other studies [19][20][21][22][23][24]. The concentration of oral disease in the population was estimated by the oral disease burden (ODB) variable, which was the outcome of this study.…”
Section: Methodsmentioning
confidence: 99%